ARCHITECTURE OF CHOICE – ADVICES OF BEHAVIORAL ECONOMICS - Terziev, Venelin (Journal of Economic Development, Environment and People, 2017)
THE NEW BOOK BY PROFESSOR DIMITAR KANEV A book review by Venelin Terziev Dimitar Kanev is professor and doctor of economic sciences. He is one of the known and established Bulgarian scientists, whose major interests are connected with the general economic theory, behavioural theory, economics and management of education and economics of labour. He is professor at Nikola Vaptsarov Higher Naval School in Varna and at Chernorizets Hrabar Varna Free University.